Acupuncture for the treatment of diabetic peripheral neuropathy in the elderly: a systematic review and meta-analysis - Zhang, Xinyu; Xiao, Lingyong; Qin, Yuan; Yang, Huan; Wei, Xiangcheng; Li, Lanping; Zhao, Shiqing; Dai, Xiaoyu (Frontiers in Medicine, 2024)
Background: Diabetic peripheral neuropathy is one of the most common complications of diabetes mellitus, often causing pain or numbness in the patient's limbs, and even leading to amputation and death. Elderly patients with DPN usually have a higher morbidity and more severe results. Acupuncture has been widely used as an effective treatment for diabetic peripheral neuropathy in China. Howev er, it is still unclear that efficacy of acupuncture in the treatment of DPN. In this review, we aimed to explore the impact of acupuncture in alleviating symptoms of DPN.Method and analysis: Six databases were searched from inception to October 2023. We searched Medline, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL),and three Chinese databases including China National Knowledge Infrastructure (CNKI), Sinomed ,and WanFang.All randomized controlled trials related to the effect of acupuncture for DPN will be included. There was no restriction in language or publication year. The primary outcome is the response rate. The secondary outcomes are the TCSS、NCVs and Blood glucose before and after the treatment . Two researchers will be responsible for the selection of study, data extraction, and assessment of study quality independently. RevMan V5.1.0 Software will be used for assessing the risk of bias and synthesizing data.Results: We searched 4518 studies, among which 9 RCTs were considered eligible. Overall, acupuncture treatment had a higher response rate than controls (RR, -2.87 [95% confidence interval (CI), -5.27 to -0.48], P=0.02), and significantly alleviated the symptoms of DPN patients, reduced their blood glucose levels, and improve their nerve conduction velocities. compared with the control group. This study will provide a high-quality synthesis of current available evidence for the treatment o f DPN with this therapy clinically.The results suggested that acupuncture might be effective in improving symptoms in DPN in elderly patients. Owing to the overall low quality of the literature included , we need more large-sample, high-quality, and low-bias studies to prove it